ANALISIS INOVASI PRODUK DAN PENGARUH MODEL BISNIS SARISA MERAPI TERHADAP STRATEGI DIVERSIFIKASI PRODUK OLAHAN SALAK PONDOH DI KABUPATEN SLEMAN - Rini Handayani; Shalahuddin Shalahuddin (Yayasan Nusantara Hasana Berdikari, 2026)
Sleman Regency possesses significant potential for Salak Pondoh production, yet product diversification among MSMEs remains relatively low. This study aims to analyze the influence of Sarisa Merapi’s Business Model (X1) and Product Innovation (X2) on Product Diversification strategies (Y) within salak-based MSMEs in Sleman. The research employed a quantitative associative method with a sample of 30 MSME practitioners. Data were collected via questionnaires and analyzed using multiple linear regression through SPSS software. The results indicate that, partially, Product Innovation has a positive and significant effect on Product Diversification. Conversely, Sarisa Merapi’s Business Model has a negative and non-significant influence on Product Diversification. This suggests that merely utilizing a successful entity as a role model without internal innovation capabilities is insufficient to drive effective product diversification. Simultaneously, both variables significantly influence diversification strategies, contributing 45.9% to the variance. This study recommends the importance of enhancing internal innovation capacity and adopting appropriate technology for MSMEs to increase the value-added of agribusiness products.